Analysis of a hybrid ultrasonic horn profile using finite element analysis. (2021) - Kumar Patel, Lokesh; Kumar Singh, Aswani; Sharma, Varun; Kala, Prateek
Abstract: Ultrasonic machining is among the non-conventional machining technique which is used to machine very hard and brittle material with help of abrasives. The ultrasonic horn is the most important part of USM which amplifies the vibration available at the transducer end to attain a required amplification factor. In the present research paper, an attempt has been made to develop a new variant of ultrasonic horn which could result in maximum magnification factor with minimum induced stresses. A comparative analysis has been made among eight different horn shapes using Modal & Harmonic Analysis in commercially available finite element package i.e. ANSYS and a new design profile i.e. a hybrid horn has been presented to attain maximum amplification factor with a reduction in the equivalent stresses.